Efektivitas Sistem Kamar Sebagai Model Pencegahan Viktimisasi Struktural Dalam Pemeriksaan Kasasi Pidana - Nur Syarifah; Mohammad Kemal Dermawan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to examine the effectiveness of the Chamber System in the Supreme Court. The focus problem in this research is on which aspects the Chamber System has succeeded in preventing structural victimization and on which aspects this system needs to be improved to achieve unity in the application of law and consistency of decisions. This study uses theory of prism of crime, theory of crime prevention and theory of effectiveness. The data were collected through literature study and interviews which then analysed through a qualitative approach. This study concludes that the Chamber System has not yet effective in preventing the structural victimization, so it requires improvement in several aspects.